An intrauterine insemination audit at tertiary care hospital: A 4½ years' retrospective analysis of 800 intrauterine insemination cycles - Leena Wadhwa; Ashish Fauzdar; Sanjana Narula Wadhwa (Wolters Kluwer Medknow Publications, 2018)
Background: There are many variables that may influence the success rates of intrauterine insemination (IUI) treatment. Therefore, a regular audit program is needed for planning effective infertility treatment and improving pregnancy outcomes. Aims and Objectives: The main objective of this study was to identify the crucial predicting factors that can influence the IUI success. Materials and Methods: A retrospective analysis of 800 IUI cycles done from January, 2013 to August, 2017 in 651 couples with various etiologies of infertility. The common etiologies included female factor of ovulatory dysfunction, tubal, endocrinal, male factor, male and female factors combined, and unexplained factors. Ovulation induction was done either by clomiphene citrate (CC) alone or in combination of CC with gonadotropins or pure gonadotropins only. Human chorionic gonadotropin trigger was given when at least one dominant follicle measuring ≥18 mm with an endometrial thickness of >7 mm was obtained. IUI was done post 36 h of trigger. The double-density gradient method was the preferred method of sperm preparation. Results: In 800 cycles in corresponding 651 couples, the total outcome was 113 pregnancies (14.1%) per cycle with overall pregnancy rate (PR) per couple of 17.3%. The highest PR was observed in the patient with ovulatory dysfunction (21.2%), followed by patients with combined factor (15.1%) and male factor (14.7%). In the study, a higher PR was achieved in the female ≤25 years (18.9%) P < 0.04 with significant findings with duration of infertility ≤5 years (15.1%) having primary infertility (14.5%) with low body mass index <25 (14.1%). IUI success rate was highest in the first cycle (14.6%) followed by second cycle (14.0%) and third cycle (3.5%). Conclusion: IUI audit enables the characterization of prognostic factors to achieve improved PR. This study identifies the factors that can predict improved pregnancy outcome in women age ≤25 years and endometrium thickness between 9 and 11 mm. We also recommend IUI as a first line of infertility treatment for couples in low-income setting provided the women age and duration of infertility are acceptably low.